Outcome of first-line treatment with pembrolizumab according to KRAS/TP53 mutational status for nonsquamous programmed death-ligand 1-High (≥50%) NSCLC in the German national network genomic medicine lung cancer - Bischoff, Philip; Reck, Martin; Overbeck, Tobias; Christopoulos, Petros; Röper, Julia; Janning, Melanie; Stenzinger, Albrecht; Griesinger, Frank; Thomas, Michael (Journal of thoracic oncology, 2024)
4207 Introduction - Programmed death-ligand 1 expression currently represents the only validated predictive biomarker for immune checkpoint inhibition in metastatic NSCLC in the clinical routine, but it has limited value in distinguishing responses. Assessment of KRAS and TP53 mutations (mut) as surrogate for an immunosupportive tumor microenvironment (TME) might help to close this gap. - Methods - A total of 696 consecutive patients with programmed death-ligand 1-high (≥50%), nonsquamous NSCLC, having received molecular testing within the German National Network Genomic Medicine Lung Cancer between 2017 and 2020, with Eastern Cooperative Oncology Group performance status less than or equal to 1 and pembrolizumab as first-line palliative treatment, were included into this retrospective cohort analysis. Treatment efficacy and outcome according to KRAS/TP53 status were correlated with TME composition and gene expression analysis of The Cancer Genome Atlas lung adenocarcinoma cohort. - Results - Proportion of KRASmut and TP53mut was 53% (G12C 25%, non-G12C 28%) and 51%, respectively. In KRASmut patients, TP53 comutations increased response rates (G12C: 69.7% versus 46.5% [TP53mut versus wild-type (wt)], p = 0.004; non-G12C: 55.4% versus 39.5%, p = 0.03), progression-free survival (G12C: hazard ratio [HR] = 0.59, p = 0.009, non-G12C: HR = 0.7, p = 0.047), and overall survival (G12C: HR = 0.72, p = 0.16, non-G12C: HR = 0.56, p = 0.002), whereas no differences were observed in KRASwt patients. After a median follow-up of 41 months, G12C/TP53mut patients experienced the longest progression-free survival and overall survival (33.7 and 65.3 mo), which correlated with high tumor-infiltrating lymphocyte densities in the TME and up-regulation of interferon gamma target genes. Proinflammatory pathways according to TP53 status (mut versus wt) were less enhanced and not different in non-G12C and KRASwt, respectively. - Conclusions - G12C/TP53 comutations identify a subset of patients with a very favorable long-term survival with immune checkpoint inhibitor monotherapy, mediated by highly active interferon gamma signaling in a proinflammatory TME.
Online verfügbar: 13. Dezember 2024, Artikelversion: 6. Mai 2024